Strategi Pengembangan Komoditas Buah Nanas Lokal di Kecamatan Matan Hilir Selatan Kabupaten Ketapang - Arianti, Ira; Cholid, Irfan (Politeknik Negeri Ketapang, 2024)
This study aims to formulate a strategy for developing local pineapple commodities in Matan Hilir Selatan Subdistrict, Ketapang District. The research method employed is qualitative, utilizing qualitative descriptive analysis to comprehend the potential and obstacles of local pineapple commodity development, and SWOT analysis to formulate development strategies. The research findings indicate that the position of local pineapple commodities in Matan Hilir Selatan Subdistrict lies within Quadrant I, with the S-O strategy being the most effective and efficient for its development. The implementable S-O strategies encompass the development of local pineapple farming by optimizing farmer expertise, maintaining pineapple as a superior product, and encouraging innovation in other processed products.